Polymerization of Lactic Acid Using Microwave and Conventional Heating; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Bakibaev A. A. Abdigali Abdimanapovich; Gazaliev A. M.; Kabieva S. K.; Fedorchenko V. I.; Guba G. Ya. Galina Yakovlevna; Smetanina E. I. Evgeniya Ilinichna; Dolgov I. R.; Gulyaev R. O. Roman Olegovich (2015, 2015)
Title screen